A Comprehensive Study of various Multi-Area Hybrid Power Systems for Generation Control - Bibhu Prasad Ganthia; Praveen B M (International Journal of Electrical Power and Machine Systems, 2025)
This paper is a detailed examination of multi-area hybrid power systems in the control of the generation taking into consideration the two area up to five area connected networks. As renewable energy sources are more and more integrated, and modern grids become more and more complex, the stability of the system itself and the frequency regulation have risen to a major issue. The study highlights the significance of Automatic Generation Control (AGC) and Load Frequency Control (LFC) in the process of integrated functionality of the various energy sources which include thermal, hydro, gas, solar, wind and energy storage facilities (ESS). Comparison of evaluations of a 2-area, 3 area, 4 area and 5 area models show the gradual increase in complexity of the system, the tie-line interaction, and communication requirements. The paper further demonstrates how traditional PID based controllers have been replaced with intelligent and decentralized AGC mechanisms, which combine optimization and artificial intelligence-based methods to improve dynamic performance. Findings suggest that, despite the fact that five-area hybrid systems are highly efficient and resilient, they need strong control frameworks and complex monitoring systems to deal with the nonlinearities and the uncertainties that are caused by renewable penetration. The results offer compelling information on how to design and optimize the smart, adaptive, and sustainable future power grids in a multi-area hybrid structure.
Keywords: Frequency control; Intelligent control; Load frequency stability; multi-Area hybrid power system; optimization techniques; renewable energy integration